Tea plantation slope position modulates nutrient and heavy metal allocation in tea plant organs: implications for health risks and sustainable plantation management - Chen, Liming; Chen, Yao; Ao, Jiahong (Frontiers in Agronomy, 2025)
IntroductionSlope position is a crucial topographic factor influencing tea plant growth and element accumulation, yet its impact on nutrient uptake and metal distribution across organs remains unclear.MethodsThis study analyzed stems, mature leaves, litter, young leaves, and tea fruits collected from upper, middle, and lower slopes of low mountainous and hilly tea plantations. Concentrations of nitrogen (N), phosphorous (P), potassium (K), iron (Fe), manganese (Mn), copper (Cu), zinc (Zn), cadmium (Cd), lead (Pb), and chromium (Cr) were measured across plant organs with respect to slope position.Results and discussionThe N, P, and K contents in organs from upper slopes were significantly higher (by 29.33%–52.25%, 14.59%–80.58%, and 16.20%–85.19%, respectively) than those from lower slopes, with the most pronounced enrichment occurring in fruits and young leaves. Fe and Mn accumulation was significantly elevated in stems, leaves, and tea fruits at the upper and middle slopes, respectively. Cu enrichment observed in mature leaves (upper slope) and young leaves (lower slope), while Zn accumulation was highest in young leaves and fruits on lower slopes. Cd and Pb were primarily concentrated in mature leaves at upper slopes, whereas Cr was significantly elevated across all organs, especially stems and fruits, at lower slopes. Health risk assessment revealed total hazard quotients (THQ) remained within safe limits (0.194–0.233), but total carcinogenic risks slightly exceeded 1×10–4 at both upper (1.05×10-4) and lower (1.15×10-4) slopes, primarily driven by Cd (93.9%) on upper slopes and Cr (70.4%) on lower slopes. These results advocate for slope-specific management strategies in low hilly tea plantations, entailing coordinated regulation of both fertilization practices and pollution sources to ensure product safety as well as mitigate toxic element accumulation.